2013
DOI: 10.1158/1541-7786.mcr-13-0229
|View full text |Cite
|
Sign up to set email alerts
|

Loss of a Negative Feedback Loop Involving Pea3 and Cyclin D2 Is Required for Pea3-Induced Migration in Transformed Mammary Epithelial Cells

Abstract: The Ets family transcription factor Pea3 (ETV4) is involved in tumorigenesis especially during the metastatic process. Pea3 is known to induce migration and invasion in mammary epithelial cell model systems. However, the molecular pathways regulated by Pea3 are still misunderstood. In the current study, using in vivo and in vitro assays, Pea3 increased the morphogenetic and tumorigenic capacity of mammary epithelial cells by modulating their cell morphology, proliferation, and migration potential. In addition,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…In mCDS, the top upregulated Cyclin D gene was Ccnd2 . A previous report showed that transcription of Ccnd2 is directly regulated by ETV4 (32), suggesting that Ccnd2 upregulation is achieved by multiple PEA3 family proteins induced by CIC-DUX4 in CDS. Therefore, the CCND2 can be used as an informative diagnostic tool, though CCND1 expression is also enhanced.…”
Section: Discussionmentioning
confidence: 98%
“…In mCDS, the top upregulated Cyclin D gene was Ccnd2 . A previous report showed that transcription of Ccnd2 is directly regulated by ETV4 (32), suggesting that Ccnd2 upregulation is achieved by multiple PEA3 family proteins induced by CIC-DUX4 in CDS. Therefore, the CCND2 can be used as an informative diagnostic tool, though CCND1 expression is also enhanced.…”
Section: Discussionmentioning
confidence: 98%
“…Since the entire study cohort showed high ETV1/4/5 expression, we further evaluated the expression of downstream targets of ETV1/4/5 . Among them only SPRED2, NOTCH1 , and CCND2 were up‐regulated compared with other soft tissue tumors studied on the same RNAseq platform.…”
Section: Discussionmentioning
confidence: 99%
“…SPRED2 is a negative regulator of Ras/Raf‐1/ERK signaling pathway and is also up‐regulated in GIST, another tumor with high ETV1 expression. NOTCH1 and CCND2 were reported as downstream targets of ETV4 . NOTCH1 signaling pathway plays an important role in embryonic development, whereas CCND2 encodes cyclin D2 that controls cell cycle progression from G1 to S phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now generally believed that Pea3-induced tumorgenicity is mediated through the increased secretion of MMPs, such astromelysin-1 as well as type I and IV collagenases, although the precise mechanism is largely unknown [115,125]. Moreover, a novel functional role of Pea3 in tumorigenesis has recently been described, where it exerts a negative feedback loop to downregulate Cyclin D2 expression during TGF-b induced EMT, leading to increased cell migration [126]. Other proteins such as vimentin, intercellular adhesion molecule (ICAM-1) and cyclooxygenase 2, have also been reported to be upregulated by Pea3 [127][128][129].…”
Section: Polyomavirus Enhancer Activator 3 (Pea3)mentioning
confidence: 99%